Medicaid, the State Children's Health Insurance Program (SCHIP), and Health Insurance : FY2008 Budget Issues. (U.S. Congressional Research., 2007)
Examines proposals contained in the Administration FY2008 budget related to Medicaid, the State children's health insurance program, and health insurance. Provides relevant background and describes each proposal.